2017
DOI: 10.1007/s00441-017-2691-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the receptor for advanced glycation end-products (RAGE) protects from secondhand smoke (SHS)-induced intrauterine growth restriction IUGR in mice

Abstract: Intrauterine growth restriction (IUGR) is a disease affecting 10% of all pregnancies. IUGR is associated with maternal, fetal, or placental abnormalities. Studies investigating the effects of secondhand smoke (SHS) exposure and IUGR are limited. The receptor for advanced glycation end-products (RAGE) is a pro-inflammatory transmembrane receptor increased by SHS in the placenta. We tested the hypothesis that inhibition of RAGE during SHS exposure protects from smoke-induced IUGR. C57BL/6 mice were exposed to SH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 53 publications
1
16
0
2
Order By: Relevance
“…The RAGE-ligand interaction is well-recognized for its modulation of chronic inflammatory diseases, such as type 2 diabetes, varieties of neurodegeneration, and chronic obstructive pulmonary disease [17,18]. More recently, our laboratory showed that increased placental expression of membrane bound RAGE contributes to low trophoblastic survival and insufficient invasion in a model of IUGR, suggesting a role of RAGE during placental disease [19]. Although membrane bound RAGE is predominately known for its function in inflammatory signaling, the nuclear isoform of RAGE (~64 kDa) was recently identified and demonstrated to be a positive regulator during DNA-DSB repair in the lungs via HRR.…”
Section: Introductionmentioning
confidence: 92%
“…The RAGE-ligand interaction is well-recognized for its modulation of chronic inflammatory diseases, such as type 2 diabetes, varieties of neurodegeneration, and chronic obstructive pulmonary disease [17,18]. More recently, our laboratory showed that increased placental expression of membrane bound RAGE contributes to low trophoblastic survival and insufficient invasion in a model of IUGR, suggesting a role of RAGE during placental disease [19]. Although membrane bound RAGE is predominately known for its function in inflammatory signaling, the nuclear isoform of RAGE (~64 kDa) was recently identified and demonstrated to be a positive regulator during DNA-DSB repair in the lungs via HRR.…”
Section: Introductionmentioning
confidence: 92%
“…Increased invasion induced by the flavoring alone was improved when 6 mg nicotine was included in the Red Hot flavoring (b). Invasion experiments were conducted with an n = 10 as outlined in the Methods section and statistically different values are noted as *p < .05 determine to what extent cytokine release was regulated by eCig treatment, we performed protein assays that simultaneously screened key inflammatory cytokines observed during periodontal disease and compared expression to cells exposed to CSE as a positive control (Lewis et al, 2017;Sanders et al, 2017). The concentration of IFN-γ, IL-1β, IL-12, IL-4, IL-6, IL-10, IL-12, IL-17, MIP1-α, MMP-9, Osteoprotegerin, Osteopontin, Osteoactivin, RANK, TGFβ1, and TNFα released into cell culture media was below the levels of detection; thus, we were not able to accurately determine their concentrations in the media from either control or treated cells.…”
Section: Rage and Cytokine Releasementioning
confidence: 99%
“…Considering the long‐term consequences of intrauterine growth restriction, many animal models have been used to simulate what is observed in humans, including the effects of restricted calories and proteins from the maternal diet, fetal hypoxia, passive smoking and hyperthermia (Barry et al., 2006; Ganguly, Touma, Thamotharan, De Vivo, & Devaskar, 2016; Lewis et al., 2017; Rueda‐Clausen et al., 2011). For instance, in rats, IUGR, produced by bilateral uterine artery ligation, was shown to determine glucose intolerance and insulin resistance at an early age, and marked elevation of glucose levels in 26‐week‐old offspring (Simmons, Templeton, & Gertz, 2001); maternal stress was also associated with IUGR and resulted in a long‐lasting disturbance in feeding behaviour and dysfunctions related to type 2 diabetes mellitus (Lesage et al., 2004).…”
Section: Introductionmentioning
confidence: 99%